Oxidative dissolution of chalcopyrite in ferric media: an x-ray photoelectron spectroscopy study - Parker, Andrew Donald (Curtin University, 2008)
The oxidative dissolution of chalcopyrite in ferric media often produces incomplete copper recoveries. The incomplete recoveries have been attributed to inhibition caused by the formation of a metal deficient sulphide and the deposition of elemental sulphur and jarosite. Although these phases have been qualitatively identified on the surface of chalcopyrite, none have been quantitatively identified. The aim of the project was to quantitatively analyse the surface before and after oxidative dissolution, with X-ray photoelectron spectroscopy (XPS), and to use the phases identified as the basis for mechanisms of dissolution and inhibition.XPS analysis was performed on chalcopyrite massive fractured under anaerobic atmosphere and chalcopyrite massive and concentrate oxidised in 0.1 M ferric sulphate (pH 1.9) and 0.2 M ferric chloride (pH 1.6) at 50, 65 and 80ºC. Quantitative XPS analysis of the chalcopyrite surfaces required the development of programs that accounted for the observed XPS spectra. The output of these programs was used to construct profiles of the chalcopyrite surfaces and the deposited phases. These surface profiles were correlated with copper recoveries determined for chalcopyrite concentrate dissolution under the same conditions.The surface of chalcopyrite before oxidative dissolution reconstructs to form a `pyritic' disulphide phase. This phase is oxidised in ferric media to form thiosulphate via the incorporation of oxygen atoms from the hydration sphere. The thiosulphate reacts in the oxidising conditions of low pH to form elemental sulphur, sulphite and sulphate. The sulphate complexes with ferric to produce hydronium jarosite. This reaction occurs at the surface during the initial stages of dissolution and in the bulk solution during the latter stages. This precipitation of hydronium jarosite during the latter stages of dissolution corresponds to inhibition of the dissolution reaction. It is therefore concluded hydronium jarosite is responsible for inhibiting the oxidative dissolution of chalcopyrite in ferric media.The identification of hydronium jarosite as the inhibiting phase is consistent with the industrial practice of removing `excess' iron from the ferric solution before oxidative dissolution. However, additional iron and sulphate are generated at the chalcopyrite surface during oxidative dissolution. These high iron and sulphate concentrations combine with the low pH and high temperatures favoured for the oxidative dissolution of chalcopyrite to produce ideal conditions for jarosite precipitation. Therefore, pH must be lowered further to prevent jarosite precipitation and enhance copper recoveries from chalcopyrite in ferric media.